Knowledge management in organizations : 13th International Conference, KMO 2018, Žilina, Slovakia, August 6-10, 2018, proceedings /: 13th International Conference, KMO 2018, Žilina, Slovakia, August 6-10, 2018, proceedings. ([2018]) - Unknown
No abstract available